Analysis of the innovation value chain in strategic projects of the Brazilian Army. Issue 4 (6th September 2019) - Ramalho, Tarso Souza; Tarraco, Elisangela Lazarou; Yokomizo, Cesar Akira; Bernardes, Roberto Carlos
Abstract : Purpose: The purpose of this paper is to describe and compare seven case studies of strategic innovation projects of the Brazilian army; these projects present high transformational potential and high investments and are supported by technology and science policies. Design/methodology/approach: The authors present herein multiple case studies in which the authors conduct a documentary analysis of the innovation processes in the Brazilian army, as well as semi-structured interviews conducted with eight servicemen with more than 15 years of working experience. Findings: The results obtained suggest that the innovation process occurs in four stages: creation, selection, development and diffusion of ideas. Practical implications: The research is relevant because it presents how the interaction between the Brazilian army, companies and academia strengthens the innovation ecosystem, stimulating the development of best practices for the management of strategic projects. Originality/value: The main contribution of this study is to present the strategic project management of innovation based on public policies and investment in projects of the Brazilian army, which are drivers for the development of ecosystems that promote the creation and expansion of companies, the diffusion of technological knowledge in universities, and suitable solutions for the military sector.